2019
DOI: 10.1029/2019ja026848
|View full text |Cite
|
Sign up to set email alerts
|

The Variation of Resonating Magnetospheric Field Lines With Changing Geomagnetic and Solar Wind Conditions

Abstract: Standing ultralow frequency waves redistribute energy and momentum around the Earth's magnetosphere. The eigenfrequencies of these standing waves can be measured by applying the cross‐phase technique to ground magnetometer data. To make a detection, the flux tubes in the vicinity of the magnetometers must all be driven at their local eigenfrequencies by a source with a sufficient frequency width. Therefore, successful measurement of the local eigenfrequencies indicates that a broadband source is exciting the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 95 publications
3
16
0
Order By: Relevance
“…With asymmetries in magnetic field configuration as described by the TS05 model removed, the asymmetry persists and consequently must be caused by plasma mass density asymmetry. This asymmetry in MLT is well documented (e.g., Poulter et al, 1984;Sandhu, Yeoman, James, et al, 2018;Takahashi & McPherron, 1984;Takahashi et al, 2016;Wharton et al, 2018;Wharton, Wright, Yeoman, James, et al, 2019), and we confirm that this asymmetry persists throughout all phases of a geomagnetic storm. The higher plasma mass densities in the afternoon lower the Alfvén speed in this sector.…”
Section: Causes Of the Variation In The Eigenfrequencies: L >supporting
confidence: 89%
See 2 more Smart Citations
“…With asymmetries in magnetic field configuration as described by the TS05 model removed, the asymmetry persists and consequently must be caused by plasma mass density asymmetry. This asymmetry in MLT is well documented (e.g., Poulter et al, 1984;Sandhu, Yeoman, James, et al, 2018;Takahashi & McPherron, 1984;Takahashi et al, 2016;Wharton et al, 2018;Wharton, Wright, Yeoman, James, et al, 2019), and we confirm that this asymmetry persists throughout all phases of a geomagnetic storm. The higher plasma mass densities in the afternoon lower the Alfvén speed in this sector.…”
Section: Causes Of the Variation In The Eigenfrequencies: L >supporting
confidence: 89%
“…Further to this, Wharton, Wright, Yeoman, and Reimer (2019) developed a Lomb‐Scargle (LS) cross‐phase technique that could process unevenly spaced data and use a higher frequency resolution because the frequency grid is independent of the properties of the data used. The chosen resolution was 4 times that achievable with a discrete fourier transform as this value was adopted in previous studies which used LS (e.g., Bland et al, 2014; Wharton, Wright, Yeoman, James, et al, 2019; Wharton, Wright, Yeoman, & Reimer, 2019). The dynamic cross‐phase spectrum uses a 40‐min sliding window, which gives a frequency resolution of 0.417 mHz without oversampling for the IMAGE magnetometer resolution.…”
Section: Cross‐phase Superposed Epoch Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These broadband fluctuations are associated with FLRs in the substorm onset region exhibiting complex features with propagation in different directions, usually in the azimuthal and radial directions. Wharton et al (2019) reported that the eigenfrequencies of any magnetic flux tube depended upon its length, the variation of the Alfvén speed along the flux tube, and the wave polarization. The Alfvén speed is determined by the local plasma mass density and local magnetic field strength.…”
Section: Discussionmentioning
confidence: 99%
“…For example it has been demonstrated that ULF wave power is enhanced during elevated solar wind conditions (e.g., Anderson, 1994; Bentley et al, 2019; Murphy et al, 2011; Pahud et al, 2009; Rae et al, 2012; Takahashi & Ukhorskiy, 2007) and enhanced geomagnetic activity (e.g., Brautigam et al, 2005; Hartinger et al, 2015; Ozeke et al, 2014). These intervals of elevated ULF wave power can manifest as localized field line resonances (FLRs) (e.g., Mann et al, 2002; Rae et al, 2005), broadband‐driven FLRs that can exhibit multiple harmonics at a fixed location or a spectrum of resonances throughout the magnetosphere (e.g., Hasegawa et al, 1983; Takahashi & McPherron, 1982, 1984; Wharton et al, 2019), as well as enhanced broadband wave power (e.g., Murphy et al, 2011; Sarris, 2014). It has also been demonstrated, in both case and statistical studies, that these periods of enhanced ULF wave power are strongly related to the dynamics of energetic electrons in the outer radiation belt (e.g., Mann et al, 2013; Mathie & Mann, 2001; Murphy et al, 2020; O'Brien et al, 2001; Olifer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%